Iron Brothers: The Strategic Bond between China and Pakistan - M Jashim Uddin (Journal of Liberty and International Affairs, 2024)
China and Pakistan have established a robust strategic partnership driven by shared geopolitical and geoeconomic interests. Often referred to as the “Iron Brothers”, their relationship has demonstrated remarkable resilience, enduring misunderstandings and differences even under challenging circumstances. China’s strategic and security priorities in South Asia and the Indian Ocean region align closely with Pakistan’s military and economic objectives, forming a strong basis for sustained cooperation. Additionally, their shared rivalry with India and the perceived threats from India and its allies further reinforce their alliance. This article examines the Sino-Pakistani partnership through the lens of balance of power and security dilemma theories, highlighting the key factors underpinning their enduring relationship. It concludes that, despite potential challenges, both nations are poised to strengthen their collaboration in pursuit of mutual military, geopolitical, and economic objectives.